1998
DOI: 10.1086/301997
|View full text |Cite
|
Sign up to set email alerts
|

The Power to Detect Linkage in Complex Disease by Means of Simple LOD-Score Analyses

Abstract: Maximum-likelihood analysis (via LOD score) provides the most powerful method for finding linkage when the mode of inheritance (MOI) is known. However, because one must assume an MOI, the application of LOD-score analysis to complex disease has been questioned. Although it is known that one can legitimately maximize the maximum LOD score with respect to genetic parameters, this approach raises three concerns: (1) multiple testing, (2) effect on power to detect linkage, and (3) adequacy of the approximate MOI f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
168
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(176 citation statements)
references
References 15 publications
7
168
1
Order By: Relevance
“…However, it has been suggested that twopoint analysis with a simple genetic model with reduced penetrance has the power to detect linkage for a trait with a complex mode of inheritance. 21 The reduced penetrance makes the model robust enough to detect linkage and it mimics the effect of multiple loci. 21 In addition, the high gene frequency specified in the model of Klar makes the model more robust as it allows for the parents passing on either haplotype if they are homozygous for the trait locus.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been suggested that twopoint analysis with a simple genetic model with reduced penetrance has the power to detect linkage for a trait with a complex mode of inheritance. 21 The reduced penetrance makes the model robust enough to detect linkage and it mimics the effect of multiple loci. 21 In addition, the high gene frequency specified in the model of Klar makes the model more robust as it allows for the parents passing on either haplotype if they are homozygous for the trait locus.…”
Section: Discussionmentioning
confidence: 99%
“…Linkage analysis was performed using the LINKAGE package, 27 under two arbitrary models, one dominant (disease allele frequency: 0.01; penetrance in heterozygotes and homozygotes: 0.5; phenocopy rate: 0.0), and one recessive (disease allele frequency: 0.01; penetrance in homozygotes: 0.5; phenocopy rate: 0.0), for a recombination fraction = 0.0. For each marker, a corrected parametric linkage score depending on these two results (MMLS-c) was obtained as the maximum of both lod score values, reduced by 0.30 according to a method proposed by Greenberg et al 28 Fine exploration of chromosome 2 region was performed on a total of 107 individuals, including the first set of 92 individuals used for genome-wide screening. Linkage analysis was performed, using the same statistics as for the genome screening.…”
Section: Methodsmentioning
confidence: 99%
“…However, linkage detection with parametric approaches is well-known to be robust to parameter misspecification, 61,70,71 with only modest reduction in power to detect linkage 61,72 even under multilocus inheritance models that are analyzed under single locus models. 73 An inflated trait allele frequency or consequent contribution to the variance is the major expected effect of failure to adjust for ascertainment. 74 This inflated allele frequency may actually be beneficial for robust linkage detection and relatively accurate localization because artificially high trait allele frequencies can compensate for model misspecification in model-based linkage analysis.…”
Section: Statistical Analysesmentioning
confidence: 99%